Regulation, Institutions and Aggregate Investment: New Evidence from OECD Countries - Balazs Egert (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper investigates the relationship linking investment (capital stock) and structural policies. Using a panel of 32 OECD countries from 1985 to 2013, we show that more stringent product and labour market regulations are associated with less investment (lower capital stock). The paper also sheds light on the existence of non-linear effects of product and labour market regulation on the capital stock. Several alternative testing methods show that the negative influence of product and labour market regulation is considerably stronger at higher levels. The paper uncovers important policy interactions between product and labour market policies. Higher levels of product market regulations (covering state control, barriers to entrepreneurship and barriers to trade and investment) tend to amplify the negative relationships between product and labour market regulations and the capital stock. Equally important is the finding that the rule of law and the quality of (legal) institutions alters the overall impact of regulations on capital deepening: better institutions reduce the negative effect of more stringent product and labour market regulations on the capital stock, possibly through the reduction of uncertainty as regards the protection of property rights.
Keywords: E24; C13; C23; C51; L43; L51; 330; aggregate investment; capital deepening; structural policy; product market regulation; labour market regulation; policy interaction; OECD